Science in the Cloud: Lessons from Three Years of Research Projects on Microsoft Azure - Gannon, Dennis; Fay, Dan; Green, Daron; Ye, Wenming; Takeda, Kenji (2014)
Microsoft Research is now in its fourth year of awarding Windows Azure cloud resources to the academic community. As of April 2014, over 200 research projects have started. In this paper we review the results of this effort to date. We also characterize the computational paradigms that work well in public cloud environments and those that are usually disappointing. We also discuss many of the barriers to successfully using commercial cloud platforms in research and ways these problems can be overcome.